Discordant biological parameters of remission in acromegaly do not increase the risk of hypertension or diabetes: a study with the Liege Acromegaly Survey database - Amodru, V; Petrossians, P; Colao, A; Delemer, B; Maione, L; Neggers, S J C M M; Decoudier, B; Kamenicky, P; Castinetti, F; Hana, V; Pivonello, R; Carvalho, D; et al. (Endocrine, 2020)
PURPOSE: Acromegaly is a rare disease due to growth hormone (GH)-secreting pituitary adenoma. GH and IGF-1 levels are usually congruent, indicating either remission or active disease; however, a discrepancy between GH and IGF-1 may occur. We aimed to evaluate the outcome of diabetes mellitus (DM) and hypertension (HT) in acromegalic patients with congruent GH and/or IGF-1 levels vs. discordant biochemical parameters. METHODS: Retrospective analysis of the data of 3173 patients from the Liege Acromegaly Survey (LAS) allowed us to include 190 patients from 8 tertiary referral centers across Europe, treated by surgery, with available data concerning DM and HT both at diagnosis and at the last follow-up (LFU). We recorded the number of anti-HT and anti-DM drugs used at the first evaluation and at LFU for every patient. RESULTS: Ninety-nine patients belonged to the REM group (concordant parameters), 65 patients were considered as GHdis (high random GH/controlled IGF-1), and 26 patients were considered as IGF-1dis (high IGF-1/controlled random GH). At diagnosis, 72 patients (37.8%) had HT and 54 patients had DM (28.4%). There was no statistically significant difference in terms of the number of anti-HT and anti-DM drugs at diagnosis versus LFU (mean duration: 7.3 ± 4.5 years) between all three groups. CONCLUSION: The long-term outcome of DM and HT in acromegaly does not tend to be more severe in patients with biochemical discordance in comparison with patients considered as in remission on the basis of concordant biological parameters, suggesting that patients with biochemical discordance do not require a closer follow-up.
Keywords: Hypertension; lidé; lidský růstový hormon; Human Growth Hormone; adenom; Diabetes Mellitus; Humans; diabetes mellitus; riziko; akromegalie; retrospektivní studie; Acromegaly; Europe; hypertenze; Insulin-Like Growth Factor I; insulinu podobný růstový faktor I; Risk; Retrospective Studies; Evropa; Adenoma